Organizational learning and job performance of teachers at public school - Quispe Huarcaya, Elizabeth (2017)
The purpose of this article is to indicate the probable bonds between organizational learning and job performance of teachers at public school of Chosica:Nicolás de Piérola, Josefa Carrillo, Emilio del Solar, Pablo Patrón, and Aplicación school. To reach this purpose, descriptive correlational, was taken to 157 teachers who were applied the two instruments: Inventory of Organizational Learning and job performance. The studies indicate that organizational learning and job performance of teachers from Chosica have a significant relation. Also, there are significant differences between Organizational Learning and job performance among public teachers of the district. Teachers from Nicolás de Pierola and Emilio del Solar beat others teachers from Chosica school in both study variables.